Road Motion Control Electric Vehicle with Speed and Torque Observer - Foito, Daniel José Medronho (2014)
This paper presents an electric vehicle (EV) with two independent rear wheel drives and with an electric differential system. A model of the vehicle dynamic model is presented. The electric differential was implemented assuring that, in straight right trajectory, the two wheels drives roll exactly at same velocity and, in curve, the difference between the two velocities assure a vehicle trajectory. A speed and torque observer for DC motor was also proposed and simulated. Analysis and simulation results of the proposed system are presented.